A literature study on lacquer poison - Kyoung-Min, Lee; Ki-Rok, Kwon; Sung-Mo, Choi; Tae-Hee, Kim (Korean Pharmacopuncture Institute, 2002)
Objective: It will be examined in this research whether Lacquer poison can be used as an distinguished treatment to cure incurable diseases by considering literature existing and various papers. Method: I studies origin, alias, species, toxicity, effect, treatment, component, medical action and contraindication of Rhus vemiciflua stokes through various kinds literatures. Results: Sap of Rhus vemiciflua stokes that is used for medical purposes, has an effect on anti-tumor, anti-oxidation, hangover cure, and gastritis suppression. Even though urushiol and fIavonoids, the main ingredient of lacquer, has medical cure effects. but urushiol results in a dermatropic allergy. Sincc xylem of a Rhus vemiciflua stokes, however. does not induce the allergy but has medical efficacy, research on this topic is needed.